PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERFIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN IPS SEJARAH DI SMPN 1 SIDOARJO - Mukhammad Farid Imanulloh; Izzatul Fajriyah; Muhammad Faris Abdil Aziz (LPPM STKIP PGRI Sidoarjo, 2023)
Problem Based Learning is a learning model that will be used as an experiment in class and this model is expected to improve the quality of learning to be more effective and efficient. Through Problem Based Learning the learning that will be obtained is through the process towards understanding the resolution of a problem. Critical thinking is one of the assets that students must have in this century. Critical Thinking is the ability to create or find an idea and idea in solving a problem. The learning approach empowering the rules of connection will fully involve literacy and critical thinking of students to explore existing knowledge and information, in order to discuss and study the material being discussed. This study aims to determine the effect of the Problem Based Learning learning model on the learning process and students' critical abilities. The research design is defined as a strategy to set the research background so that the researcher obtains valid data according to the variable characteristics and the researcher's objectives. This research is a true experiment type. This study took the Pre-test-Posttest control group design research design which aims to determine the effect of the Problem Based Learning learning model on critical thinking in social studies subjects, by comparing one experimental group that was treated with the Problem Based Learning learning model and the other group was given the model learning Discovery Learning. The subjects of this study were class VII students of SMP Negeri 1 Sidoarjo for the 2022/2023 academic year, which consisted of two classes. From the results of research conducted with the ability to think critically and learning outcomes (Gain Score) proves that the experimental class is superior to the control class.